PENGARUH RASIO KEUANGAN TERHADAP PERINGKAT OBLIGASI DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - M. Arbai Hadi Susanto; Nugroho Mardi Wibowo; Hadi Susanto (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
The purpose of this research is to describe the condition of liquidity ratios, leverage, profitability, and earnings management as well as the ratings of the bonds of companies listed on the Indonesia Stock Exchange in 2019-2021. Analyzing the direct effect of liquidity ratios, leverage and profitability on the company's earnings management. Analyzing the direct influence between liquidity ratios, leverage and profitability as well as earnings management on the Company's bond ratings. Analyzing the indirect effect of liquidity ratios, leverage and profitability on the Company's bond ratings through earnings management. This research is classified as causal associative research with a quantitative approach. The population in this study are companies registered on the IDX and issue bonds and get a rating from PT Pefindo during the 2019-2021 period with a total population of 54 companies. The sampling technique used the census method. The population in this study are mining companies that are registered and actively traded on the Indonesia Stock Exchange (IDX) for the 2017-2021 period with the sampling technique used in this study is purposive sampling so that 10 companies are obtained as research samples. This study uses PLS as a confirmatory theory and to analyze the effect or test the proposed hypothesis. The data analysis technique uses Partial Loast Square with the help of Smart PLS Software. The results of the study indicate that the company's liquidity is able to meet short-term liabilities. The company's average leverage is 3.58%. Profitability is 5.36% of the company's total assets. The average company earnings management is 0.0019. The company's average bond rating has an idA+ rating. Liquidity variable has no significant negative effect on earnings management, leverage has no significant positive effect on earnings management, profitability has a significant positive effect on earnings management, liquidity has a significant negative effect on bond ratings, leverage has a significant positive effect on earnings management. bond rating, profitability does not have a significant effect with a positive direction on bond ratings, earnings management has a significant negative effect on bond ratings, liquidity does not have a significant effect on bond ratings through earnings management, leverage has no significant effect on bond ratings through earnings management. earnings management, profitability has no significant negative effect on bond ratings through earnings management in companies listed on the Indonesia Stock Exchange he Year 2019-2021..